PEMANFAATAN FILTER ZEOLIT UNTUK MENINGKATKAN KUALITAS BIOGAS BERBAHAN BAKU SAMPAH ORGANIK BUAH-BUAHAN - Esty Asma Dewanti (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2014)
Biogas is a gas fuel which is renewable and eco-friendly, content in biogas consists of H2O, CO2, CH4, and H2S. The content of carbon dioxide (CO2) gas high enough in the biogas to heat value decreased during the combustion process, so the process of purification is needed to separate the gas content. One method of purification is to use a zeolite adsorbent. Zeolite adsorption capability of the affected pore surface area, for it required refinement process (milling) zeolites to improve the power filter adsorption. The purpose of this research is to lower the levels of CO2 gas in biogas using milling zeolites have been in the variant time 5 minutes, 10 minutes, 15 minutes in tube purification for 60 minutes. Further analysis is done by using a Gas Analyzer to find out the CO2 gas levels before and after purification using zeolite.Keywords : Biogas, zeolit, CO2, purification, adsorption.